The impact of KRAS mutational status on patient-reported outcomes in advanced non-small-cell lung cancer: a cross sectional study in France and Germany - Chouaid, Christos; Giannopoulou, Andromachi; Starry, Alexandra; Stollenwerk, Björn; Bozorgmehr, Farastuk (Journal of medical economics, 2025)
Health-related quality of life (HRQoL) studies in patients with advanced non-small-cell lung cancer (NSCLC) according to KRAS mutational status are limited. This study aimed to report real-world evidence on HRQoL outcomes based on KRAS mutational status in patients with advanced NSCLC tumors receiving second-line or later (2L+) treatment in France and Germany. In this real-world, non-interventional, cross-sectional, multicenter, patient-reported outcome (PRO) study conducted in France (15 contributing sites) and Germany (8 contributing sites), physicians enrolled adult patients with locally advanced and unresectable or metastatic NSCLC with known KRAS mutation status (KRAS G12C, KRAS non-G12C, or KRAS wildtype [WT]), who received a 2L + treatment. Study outcomes included sociodemographic characteristics; HRQoL evaluations based on EORTC Global Health Status QoL scores (QLQ-C30) and EQ-5D-5L scores. Data were analyzed descriptively. Of 156 enrolled patients, data from 149 patients were included in the final analysis (France, n = 103; Germany, n = 46). Median (quartile [Q]1, Q3) age was 67.0 (61.0, 71.0) years; 56.4% of patients were male. In total, 38.9% (n = 58), 26.2% (n = 39), and 34.9% (n = 52) of patients had tumors with KRAS G12C mutation, KRAS non-G12C mutation and WT KRAS, respectively. Mean (±SD) QLQ-C30 Global Health Status QoL scores were 56.99 (20.30) for the overall population, and 56.03 (22.55), 58.97 (18.67) and 56.57 (19.05) for KRAS G12C, non-G12C, and WT subpopulations. In the overall population, moderate-to-extreme problems were reported in all EQ-5D-5L dimensions (range: overall population, 15.5%-39.6%; KRAS G12C, 15.6%-46.6%; non-G12C, 7.8%-23.1%; WT, 21.1%-44.2%). HRQoL was broadly similar across KRAS G12C, non-G12C, and WT subpopulations.